1996
DOI: 10.1016/0924-9338(96)80455-x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, metabolic and immune correlates of seasonal variation in violent suicide: a chronoepidemiologic study

Abstract: The purpose of this chronoepidemiologic study was to investigate the time-relationships between the yearly variations in occurrence of violent suicide in Belgium and the yearly variations in various biochemical, metabolic and immune variables in the Belgian population. The weekly mean number of deaths due to violent suicide for all of Belgium for the period 1979-1987 was computed. Twenty-six normal volunteers had monthly blood samplings during one calendar year for assays of plasma L-tryptophan (L-TRP), compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…With respect to diagnostic categories, the relationship was determined in personality and neurotic disorders, depressive disorders and male inpatients with serious suicide attempts [16,17]. However, some authors reported this relationship merely occurring in patients with violent suicide attempts [8]. For this reason, the association between suicide and cholesterol remained subject to controversy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to diagnostic categories, the relationship was determined in personality and neurotic disorders, depressive disorders and male inpatients with serious suicide attempts [16,17]. However, some authors reported this relationship merely occurring in patients with violent suicide attempts [8]. For this reason, the association between suicide and cholesterol remained subject to controversy.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Stewart and Stewart [7] no relationship between cholesterol and aggressive behaviors was found. Maes et al [8] however revealed a relationship between decreased serum cholesterol and suicide attempts only in psychiatric patients with violent suicide attempts.…”
Section: Introductionmentioning
confidence: 99%
“…The roles of meteorological and other factors as precipitous agents of suicidal activity have been widely studied. Elevated ambient temperature, low tryptophan availability, increased sunshine duration and low day-time plasma melatonin levels often precede the fatal outcomes (22)(23)(24)(25)(26). As far as melatonin and solar radiation are concerned, previous studies have not been reliable in this respect.…”
Section: Melatonin and Self-destructive Behaviormentioning
confidence: 78%
“…However, neither duration of sunshine nor cloudiness may be reliable indicators of the true amount of the light reaching the eyes, for light reflected off the ground remains underrepresented. Likewise, single daytime measurements (13), common in comparative melatonin studies, represent melatonin secretion poorly.…”
Section: Discussionmentioning
confidence: 99%